An analytical direct correlation function for hard core double Yukawa potential - Khanpour, M.; Parsafar, G.A.; Hashim, R. (Elsevier, 2010)
Using a general expression for the second term in the density expansion of the hard core potentials we obtained an analytical expression for the direct correlation function of the hard core double Yukawa potential The results of this calculation using the proposed direct correlation function and its related radial distribution function through the Ornstein-Zernike equation show good agreements with those obtained by the computer simulation of the same model (C) 2010 Elsevier BV All rights reserved